Exposure assessment in occupational and environmental epidemiology - Nieuwenhuijsen, Mark J. (Oxford : Oxford University Press, 2003)
Set against a growing public, media and political concern about occupational and environmental health issues, this text is a comprehensive reference on methods and applications in the field of exposure assessment for occupational and environmental epidemiological studies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health risk assessment; Environmental health; Occupational diseases -- Epidemiology; Environmentally induced diseases -- Epidemiology